Qur’anic worldview and the natural sciences: An ulū al-albāb integration framework for Islamic secondary schools - Hassan, Nur Jannah (Önder Akademi, 2018)
For the Muslim ummah, the issue of integration in education has been a major concern since the post-colonial period, as the events that transpired during this period left Muslims with the legacy of a dichotomous education. In turn, this type of education results in disharmonies in the person, family, society and the environment. Yet post-modern trends are opening up opportunities for non-conventional alternatives as solutions. This article presents the major rationales for integrating the Qur’anic worldview and the natural sciences. It touches upon the fundamental elements of the Qur’anic worldview in relation to the studies of nature, specifically the notion of “reading” the two Books of Allah (i.e. al-Qur’ān and the Open Book of the Cosmos) as well as humanity’s relation with Allah, with itself and with the cosmos. This article briefly discusses the worldviews that have brought about the natural sciences to their current pedestal, the ensuing environmental and humanitarian crises of the contemporary world, and experts’ responses in the face of these crises. It puts forward an integrated model for the study of the natural sciences based on a synthesis of al-Ghazālῑ’s methodology of integration and discourse on the qalb, and the Ūlū al-Albāb notion of the Qur’an. The integrated model is for use in Islamic secondary education, where certain aspects of the natural sciences undergo a discreet but holistic reposition, reinterpretation and reorientation from the framework of, and organically infused with the Qur’anic worldview. It is believed that such integration is able to address the conflicts and disharmonies, and in the long run restore the equilibrium, not just within the Muslim person and the ummah but also to bring about sustained goodness for humanity in general and the environments in which they reside.